Impact of intravitreal aflibercept dosing regimens in treatment-naïve patients with neovascular age-related macular degeneration in routine clinical practice in France: results from the RAINBOW study - Weber, Michel; Kodjikian, Laurent; Coscas, Florence; Faure, Céline; Aubry, Isabelle; Dufour, Ingrid; Cohen, Salomon Y (BMJ open ophthalmology, 2020)
ObjectiveTo evaluate 12-month outcomes in treatment-naïve patients with neovascular (wet) age-related macular degeneration (AMD) stratified by intravitreal aflibercept (IVT-AFL) regimen.Methods and analysisPatients included in the 12-month interim analysis of Real life of intravitreal Aflibercept In FraNce: oBservatiOnal Study in Wet AMD (RAINBOW), a 4-year, ongoing observational study conducted in France, were stratified by IVT-AFL dosing regimen. Safety (n=593) and effectiveness (n=428) data were analysed. Regimens included a regular cohort (three initial monthly IVT-AFL injections and ≥6 injections) and irregular cohorts (<6 injections) with and without three initial monthly injections. The main outcome measure was mean gain in best-corrected visual acuity (BCVA) at 12 months.ResultsMean number of IVT-AFL injections was 6.0 (all patients, n=513), 7.2 (regular cohort, n=102), 6.1 (irregular cohort with three initial monthly injections, n=266) and 5.2 (irregular cohort without three initial monthly injections, n=60). Overall mean gain in BCVA at 12 months was 5 letters; +7.1 letters (regular cohort) and +5.6 letters (irregular cohort with three initial monthly injections), both p<0.001 versus baseline, and –1.1 letters (irregular cohort without three initial monthly injections), p=0.669. Improvements in BCVA were also significantly greater in the regular cohort (p<0.001) and irregular cohort with three initial monthly injections (p=0.003) compared with the irregular cohort without three initial monthly injections. Ocular and non-ocular adverse events were reported in 14.7% and 17.4% of all patients, respectively.ConclusionTreatment-naïve patients with neovascular AMD receiving three initial monthly injections followed by regular or irregular injections over 12 months experienced better visual acuity outcomes than those receiving irregular treatment without three initial monthly injections.Trial registration numberNCT02279537.